Phytase Supplementation in a Reduced Calcium and Phosphorus Diet Fed to Broilers undergoing an Eimeria Challenge - Ashley L. Shaw; Kenneth S. Macklin; John. P. Blake (The Journal of Poultry Science, 2012)
This experiment was conducted to evaluate the effect of coccidial control, dietary mineral density, and coccidial challenge on broiler chick performance. Commercial broiler chicks (1008) were placed across 48 floor pens (21 birds/pen, 6 replications/treatment) on either fresh or seeded bedding. Treatments involved phytase-supplemented diets containing two Ca-NPP levels (0.5% Ca, 0.25% NPP or 0.7% Ca, 0.35% NPP), two coccidiosis control strategies (vaccination or in-feed coccidiostat), and two Eimeria exposures (unchallenged or challenged). On d 11 and 20 body weight (BW) and feed consumption (FC) were recorded for each pen. Five birds/trt were sacrificed and intestinal samples were obtained for visual and microscopic lesion scoring on these days. The left tibia was also collected for the assessment of bone strength. BW, FC, and bone strength were unaffected (P>0.05) by diet, though coccidiosis control methods had an affect on both body weight gain (BWG) and FC from 0-20d. Coccidiosis challenge led to a decline (P<0.05) in overall BWG. Regardless of treatment, visual and microscopic scoring of the duodenum and ceca showed few differences (P>0.05). The percentage of birds having lesions associated with Eimeria acervulina was increased (P<0.05) on d 20. Overall, the results indicate that bird performance and skeletal strength are not affected by decreased Ca-NPP levels when diets are supplemented with phytase, but a coccidiosis challenge will result in reduced growth performance.